EMERGENCE OF BANKING AND FINANCIAL TERMS AND FEATURES OF TERMINOLOGY - Nilufar Saliyevna Ataeva (International Journal of Innovations in Engineering Research and Technology, 2021)
The article is about banking and finance is a part of the economy and has a great influence on its terminology. It consists of general banking and financial terms (delay of payment; currency market) , special banking and financial terms (gross national product; global quota); and they in their turn are divided into groups. We know that some terms have many meanings Each meaning expresses its meaning in a specific context or speech. Terms and concepts in the field of banking are often activated in the speech of bank employees.